DEVELOPING SUPPLEMENTARY READING MATERIALS FOR THE STUDENTS OF EIGHTH GRADERS NURUS SALAFIYAH PROBOLINGGO - zainuddin zainuddin (Journal of English for Academic and Specific Purposes (JEASP), 2019)
Developing Supplementary Reading Materials for the students of eighth Graders at Nurus Salafiyah Probolinggo. It modified Latief model (2009); the researcher developed material based on data analysis taken from a preliminary study. The material was validated and tried-out to class VIII-B of Nurus Salafiyah Probolinggo. The result showed that this study and the product have successfully answered the students' needs in reading skills. Therefore, the product could be used for the eighth-grader students of Nurus Salafiyah Probolinggo